2023
DOI: 10.1021/acsaenm.2c00160
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Underwater Tribological Behavior of Hybrid Fabric Composites Using Ultrahigh Molecular Weight Polyethylene and Different Fillers

Abstract: This paper comprised a study of a method to improve underwater tribological properties of hybrid PTFE/Nomex fabric composites by ultra-high molecular weight polyethylene (UHMWPE), SiO2, and graphite. A ring-on-block tribometer was used to perform the tribological test under dry sliding and water lubrication conditions. The worn surface was analyzed by scanning electron microscope (SEM). The results showed that with the help of UHMWPE, SiO2, and graphite, the underwater friction coefficient (COF) was reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Using a combination of attapulgite nanofibers and titanium dioxide nanoparticles, Meng et al (2022) improved the frictional behavior of a UHMWPE composite and their findings showed that the fillers' network structure increased the composites' thermal stability, and the best wear resistance was achieved with a filler content of 5 Wt.%. Liu et al (2023) depicted that due to the excellent water resistance and selflubrication of UHMWPE, SiO 2 and graphite, the coefficient of friction (COF) of polytetrafluoroethylene (PTFE)/UHMWPE/ SiO 2 /graphite composites under water condition was lowered by three times, and the wear rate was reduced by approximately 40 times. Moreover, the additive can also promote the formation of lubricating layer on the worn surface during the sliding process.…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of attapulgite nanofibers and titanium dioxide nanoparticles, Meng et al (2022) improved the frictional behavior of a UHMWPE composite and their findings showed that the fillers' network structure increased the composites' thermal stability, and the best wear resistance was achieved with a filler content of 5 Wt.%. Liu et al (2023) depicted that due to the excellent water resistance and selflubrication of UHMWPE, SiO 2 and graphite, the coefficient of friction (COF) of polytetrafluoroethylene (PTFE)/UHMWPE/ SiO 2 /graphite composites under water condition was lowered by three times, and the wear rate was reduced by approximately 40 times. Moreover, the additive can also promote the formation of lubricating layer on the worn surface during the sliding process.…”
Section: Introductionmentioning
confidence: 99%